Withania somnifera: A New Ray of Hope for Cancer - Shah , Darshana R.; Palaskar , Sangeeta J.; Shah, Rajesh M.; Pawar , Rasika B. (New Advances in Medicine and Medical Science Vol. 4, 2023)
Cancer is a hyperproliferative illness defined by aberrant cell growth that invades and destroys surrounding tissues. Many cancers are inherited, while others are caused by internal and external environmental factors. Cancer treatment options include surgery, radiation, chemotherapy, and targeted therapy. Despite significant advances in drug discovery, research to understand the complex biology of cancer with new therapeutics is still ongoing. Plants with medicinal characteristics have been used by traditional medical systems throughout the world for millennia, giving modern researchers a chance to evaluate their effectiveness against diseases like cancer. Withania Somnifera (WS), commonly known as Indian Winter Cherry and Indian Ginseng, is a famous ayurvedic plant used as a traditional therapy for many cancers. According to the findings of studies on WS and its chemical components such as Withaferin A (WA), Withanolie D (WithaD), and others, it is effective in the prevention and treatment of various types of cancer such as colon, blood, lung, skin, breast, renal, fibrosarcoma, prostate, pancreatic, renal, malignant melanoma, osteosarcoma by preventing proliferation and progression of cancer cells, alteration in hematological and biochemical parameters, modulation of cell cycle markers etc. Withania somnifera can be used alone or in conjunction with synthetic medications. The discovery of new natural anticancer compounds is critical for cancer prevention and treatment. To provide complementary and alternative therapy, multicentric long-term clinical research should be conducted. This review discusses the use of WS as a potential immunomodulatory, anticancer, and chemopreventive drug and emphasises the possibility of its application in the treatment of cancer.